SYMPTOMS OF DISSOCIATIVE IDENTITY DISORDER (DID) SUFFERED BY GRACE MARKS IN MARGARET ATWOOD’S ALIAS GRACE - Ngesti Finesatiti; Sri Saraswati (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2021)
The research discussed the symptoms of Dissociative Identity Disorder (DID) suffered by Grace Marks in Margaret Atwood’s Alias Grace. As it focused on personality study, a psychoanalysis approach was used. To identify the symptoms of DID suffered by Grace Marks, Haddock’s DID theory was employed. The results showed that there were two types of symptoms i.e. physical and emotional suffered by Grace Marks. The physical symptoms were panic attack and appearance differences, while the emotional symptoms include nightmare, depression, loss of time, body memory, and switching behavior.